Problems and Development Ways of Distance Learning In Arabic Language Teaching - Sharipova, Omina (Indonesian Journal Publisher, 2025)
One of the main factors that contributed to the global spread of distance learning was the COVID-19 pandemic. During this period, both students and teachers faced numerous challenges in adapting to the new educational setting. With the transition to technology-based education, Arabic language teachers, like other language instructors, encountered difficulties in using new digital tools. Many educators initially struggled with platforms like Zoom, Google Meet, and Microsoft Teams for conducting online classes. Even though traditional classroom teaching resumed later, the need to develop and improve the distance learning model remains one of the most pressing tasks in the education sector. This article discusses several problems and solutions related to implementing distance learning in Arabic language education.